Factors that shape an EFL preservice teacher´s identity (2019)
Narratives have become lately a resource for researchers to explore in the field of education, narrative has proved especially fruitful in the study of teachers professional lives and careers (Bathmaker and Harnett, 2010; Clandinin and Connelly, 2000; Goodson and Sikes, 2001: Loughran and Russell, 2002; Webster and Mertova, 2007). This particular research project under the qualitative research study was conducted under the field of narrative inquiry approach as part of the subproject, the voices of the LLEI realities: Life stories and experiences, in order to find what factors shape an EFL pre-service teacher`s identity at LLEI-DUAD. The research narrates different events in a lifetime story in order to analyze how personal identity influence professional identity. The autobiography traced the path to build the research, data were collected using different instruments as narratives frames, written narratives, and multimodal data elements as pictures, poems, samples of lesson plans, students work and interviews. The analysis consisted of reading, re-reading, coding and categorizing the real-life information into categories and subcategories, defining and explaining each of them to finally identify the different components that are responsible for shaping the teachers’ identity. The findings demonstrated that teachers` identity is built based on two different dimensions, related to the teacher life experiences, and the pedagogical knowledge and practices and the identity is a dynamic process of becoming instead of a product. These are important findings because it is value for teachers to reflect on their own practices. These results lend ideas for future research related to the topic as well as ideas to analyze and create better pedagogical professional development and practices.